2019
DOI: 10.3390/agronomy9030155
|View full text |Cite
|
Sign up to set email alerts
|

Prohexadione-Calcium Application during Vegetative Growth Affects Growth of Mother Plants, Runners, and Runner Plants of Maehyang Strawberry

Abstract: Strawberry (Fragaria × ananassa Duch.) is an important horticultural crop that is vegetatively propagated using runner plants. To achieve massive production of runner plants, it is important to transfer the assimilation products of the mother plant to the runner plants, and not to the runner itself. Application of prohexadione–calcium (Pro–Ca), a plant growth retardant with few side effects, to strawberry is effective in inhibiting transport of assimilates to runners. This study aimed to determine the optimum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Because of effect on gibberellin inhibition, Pro-Ca decreased plant height and length between internodes of tomatoes (Altıntaş 2011), onion (El-Ghorab et al 2019, strawberries (Kim et al 2019) and eggplant (Özbay & Ergun 2015) without decreasing the number of leaves. In the current study, the similar observations were obtained until on the 50 th day in 30 mg L -1 Pro-Ca dose and until the end of the trial in 45 and 60 mg L -1 Pro-Ca doses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of effect on gibberellin inhibition, Pro-Ca decreased plant height and length between internodes of tomatoes (Altıntaş 2011), onion (El-Ghorab et al 2019, strawberries (Kim et al 2019) and eggplant (Özbay & Ergun 2015) without decreasing the number of leaves. In the current study, the similar observations were obtained until on the 50 th day in 30 mg L -1 Pro-Ca dose and until the end of the trial in 45 and 60 mg L -1 Pro-Ca doses.…”
Section: Resultsmentioning
confidence: 99%
“…Pro-Ca has a significant advantage compared to other PGRs due to its low toxicological effect and short half life in plants and soil (Bizjak et al 2012). It was determined in different plant species that the application of lower doses of Pro-Ca in post-planting period had more positive effects on plant development, yield, and fruit quality compared to its higher doses (Altuntaş 2016;Kim et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the findings in this study, Akdemir (2018) study in lettuce seedlings showed that the higher doses (100 and 150 mg L -1 ) of Pro-Ca increased stem diameter and decreased plant height and stem fresh weight, while the low dose (50 mg L -1 ) Pro-Ca increased stem fresh weight. Kim et al (2019) reported that 50 mg L -1 Pro-Ca application after planting increased fresh and dry weights of strawberry plant compared to control.…”
Section: Resultsmentioning
confidence: 97%
“…The reason for height reduction in the treatment involving G 2 can be attributed to the action of prohexadione calcium, a gibberellin biosynthesis inhibitor that acts as a co-substrate for catalyzing hydroxylations involved in the late stages of GA biosynthesis. This retardant has been reported to mainly target an enzyme 3b-hydroxylase, which helps in the conversion of inactive GA 20 /GA 9 into highly active GA 1 /GA 4 , leading to reduced plant height and shoot length (Kim et al, 2019). It was reported that chlormequat chloride used in G 4 is also an anti-gibberellin , limiting stem elongation and causing height reduction (Rademacher, 2000).…”
Section: Figure 2 Main Effects Of Stress Tolerance Promoting Bioregulators On Plant Morphological and Fruit Physical Parametersmentioning
confidence: 99%